Ecotomografía en la apendicitis Aguda - Guerra B., Marcela; Arroyo P., Alejandro; Yañez S. , Paulina (Revista Hospital Clínico Universidad de Chile, 1996)
COLOR DOPPLER ECHOTOMOGRAPHY IN THE DIAGNOSIS OF ACUTE APPENDICITIS.Acute appendicitis is the most frequent cause of surgical abdominal emergency. In most of these patients (70%) the diagnosis is based on the clinic history and on the physical examination.In those cases the clinic presentation is confusing, the ultrasound with gray scale and high frequency transducers, using the graduated compression technique, has become of great help. lt has been reported a sensibility of 84 - 96% with a specificity of 94 - 98% for this diagnostic method.Also lately it has been seen that the study with Color Doppler can be useful as help in the diagnosis of appendicitis, demonstrating a local increase in the blood flow in the appendicular wall or in the inflammatory mass. However, Color Doppler by itself does not increase the sensibility. This technique acquires its greater usefulness in those cases in which the appendicular size is limit.